Kebebasan Jual Beli Online (E-Commerce) Menurut Hukum Di Indonesia - Sahputra, Candra; Suhendro, Suhendro; Fahmi, Fahmi (Jurnal Panorama Hukum, 2022)
E-commerce is now seen to be a convenient way for merchants and buyers to do business in an effective and efficient manner. There are no longer any barriers between sellers and buyers, making it simple to conduct sales transactions at any time and from any location. The huge number of E-commerce users in Indonesia is due to the simplicity with which merchants and consumers may conduct online sales transactions. As a result, the author believes it is necessary to examine and analyze the freedom of online purchasing and selling (E-commerce) under Indonesian law. By providing and evaluating descriptive qualitative data, this research utilizes a normative legal technique. The study's findings show that the rules of E-commerce buying and selling processes can be found in the "General Dictionary of Civil Law," and that the validity of the juridical proof of electronic documents is clearly regulated in Law No. 19 of 2016 concerning Amendments of Law No. 11 of 2016 2008 Concerning Information (ITE).